The Impact of Monetary Strategies on Economic Growth: An Empirical Analysis for Pakistan - Mahmood, Hamid; Waheed, Abdul; Khalid, Samia (Asian Journal of Empirical Research, 2017)
The present study aims to check the long run relationship between monetary variables and gross domestic product. The study has used the yearly data for the periods of 30 years from 1983 to 2013. It is concluded that GDP is positively associated with M2, government expenditures, and inflation. While it is negatively related with interest rate, growth becomes possible with low interest rate. Investment opportunities are increased in economy. With currency appreciation, it has positive impact on growth. Domestic products are cheaper that compete in international markets and BOP becomes favorable. Due to increase in government borrowing from SBP for development purposes money supply increases. Money supply firstly effects the growth, and then it shows the impact on inflation. Due to the increase in the demand of goods output increases and it generates more employment opportunities. Lower interest rate encourages the investor to invest with the result employment increases. These monetary policies increase output growth through money supply which has short run effect. Most of the developing countries lag behind in attaining the objectives and goals of monetary policy. The main hurdles are to increase internal government borrowing and inflation pressure which destabilize the entire economy.